The appearance of voice: EAP and academic literacies approaches to teaching reflective writing - Simon A. Williams (Association for Learning Development in Higher Education (ALDinHE), 2019)
The increasingly common requirement for higher education courses to include reflective writing as part of assessment practices places additional demands on novice writers. Complex and self-referential assessment criteria mean that students on foundation and pre-sessional courses in particular find it hard to decode and match descriptors, and to balance subjectivity and critical analysis. English for Academic Purposes (EAP), the most widely adopted approach to teaching academic writing in higher education, prioritises objectivity, and teaches students to recognise generic patterns of text organisation – though it seldom includes reflective writing itself as a genre. In contrast, the less familiar teaching approach of academic literacies explores students’ subjectivity, more obviously relevant to reflection, often through the development of an authentic narrative voice. As in other forms of academic writing, voice in reflective writing can be seen as a construct. It conveys a persona via the narrative, and an ethos via its specialised content. However, unlike other forms of academic writing, the personain reflective writing must simultaneously communicate the author’s private and public self.